Review of edible Australian flora for colour and flavour additives: Appraisal of suitability and ethicality for bushfoods as natural additives to facilitate new industry growth. (November 2022) - Hay, Thomas; Prakash, Sangeeta; Daygon, Venea Dara; Fitzgerald, Melissa
Abstract: Background: Edible native flora, or 'Bushfoods ' of Australia include a diverse range of novel species in terms of their flavours and natural colours . Bushfoods have been recognised for high bio-active phytonutrient content. Bushfoods are also Traditionally valuable to Aboriginal and Torres Strait Islander cultures, where industry participation facilitates capital and social benefits to remote communities. Currently, the suitability of native Australian plants for use as natural food flavouring and colourings is unknown, particularly in 'fringe' species which have minimal market adoption. Therefore, an appraisal of bushfoods suitability for natural additives is needed to promote new sector growth. Scope and approach: This review presents key fields relevant to appraising the suitability of bushfoods for development of natural additives. The relevant fields are market assessment of natural additives and consumer motivations, directions of natural compound extraction, assessment of valuable fringe bushfoods species, and ethical and technical challenges to industry participation. Key findings and conclusions: The growth of the bushfoods industry can be facilitated through natural additives development. Consumer trends are dictating industry adoption of natural food additives. Consumers are expected to be receptive of bushfoods derived additives, particularly in the Australian domestic market. Bushfoods are found to contain significant phytochemical content. Research focus on natural additive application of these compounds is presently minimal. An assessment of native Australian flora resulted in a high likelihood of identifying valuable species for natural additives investigation, with a collection of 17 fringe species being identified and summarised from literature. However, technical risks include a lack of food safety assessment of fringe species, as well as maintaining ethical development which observes Traditional Owner's rights and complies with the Nagoya Protocol . The review finds that natural additives development using bushfoods is practical, though further market surveying, food safety investigation, and ethical food industry participation are necessary to facilitate industry application. Highlights: Presents 19 new bushfoods suitable for natural additives. Describes an ethical pathway for non-indigenous industry participants. Discusses opportunities for the social and economic empowerment of indigenous people. Explores unique sources of flavours and colours.